ChemInform Abstract: N‐Arylation of Amines: C—N Coupling of Amines with Arylboronic Acids Using Fe3O4 Magnetic Nanoparticles‐Supported EDTA—Cu(II) Complex in Water. Issue 13 (March 2015) - Mostafalu, Ramin; Kaboudin, Babak; Kazemi, Foad; Yokomatsu, Tsutomu
Abstract A EDTA—Cu(II) complex supported on Fe3O4 magnetic nanoparticles is applied for the C—N coupling of arylboronic acids with amines.